The Struggle Is Real: How Residents Learn to Provide High-Value, Cost-Conscious Care. Issue 4 (8th August 2019) - Stammen, Lorette; Slootweg, Irene; Stalmeijer, Renée; Janssen, Linda; Stassen, Laurents; Scheele, Fedde; Driessen, Erik
Abstract: Phenomenon: Rising healthcare expenditures threaten the accessibility and affordability of healthcare systems. Research has demonstrated that teaching (junior) physicians to deliver high-value, cost-conscious care can be effective when learning is situated in a supportive environment. This study aims to offer insight into how residents learn to provide high-value, cost-conscious care in the workplace and how the postgraduate training environment influences this learning. Approach: Six homogeneous focus groups were held between August 2015 and July 2016 with 36 residents from six residency programs (dermatology, n  = 5; elderly care, n  = 8; family medicine, n  = 5; internal medicine, n  = 6; orthopedic surgery, n  = 6; surgery, n  = 6). An iterative grounded theory approach was used to analyze the qualitative data. Findings: Influential factors in learning of high-value, cost-conscious care delivery operated on three levels: individual resident, training program, and the workplace. On the individual level, we discerned three types of beliefs regarding HV3C. At the training program level, perceived determinants of learning included resident–supervisor interactions, involvement in decision-making over time, and exposure to variation in care delivery. At the workplace level, learning depended on the availability of professional healthcare expertise and the presence of institutional policy. Insights: Residents struggle to seize high-value, cost-conscious care learning opportunities in the workplace setting. Both residency training programs and workplaces can contribute to creating these learning opportunities. An important starting point is being aware of the different personal beliefs of residents and the approaches to high-value, cost-conscious care on the level of the training program and workplace.